A Descriptive Study of the ABC Unified School District K-6 Reading Program - Casey, Jean M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A study designed to provide insights into reading programs and materials, specifically those in the 21 elementary schools in one California school district, is described in this report. Following a brief presentation of the background of the study, the report states the 15 questions investigated and describes the variables, population, and methodology used, which included observation, classroom analysis of test scores, and analysis of parent questionnaires. Results are presented for each question and include the following areas: (1) the district's goals and objectives, (2) teacher role in preparing objectives, (3) reading materials used in the schools, (4) the effect of classroom environment on student achievement, (5) the relationship of teacher enthusiasm to reading achievement, (6) the relationship of students' reading attitudes to reading proficiency, (7) the effect of teaching method on reading achievement, (8) the amount of administrative involvement in the reading program, (9) parents' perceptions of the reading program and its effect on their children, and (10) the effect of class size on reading achievement. Extensive appendixes contain data for each school studied and copies of instruments used in the study. (FL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Techniques; Educational Research; Elementary Education; Program Content; Program Descriptions; Program Effectiveness; Program Evaluation; Reading Achievement; Reading Instruction; Reading Materials; Reading Programs; Reading Research; Teaching Methods; Reports, Research; Reports, Evaluative